Arbitration and Assimilation - Stephen J. Ware (Washington University Law Quarterly, 1999)
While largely accepting the points that Professor Spitko and I make, Professor Ron Krotoszynski suggests that we present an incomplete picture. He acknowledges the benefits we attribute to privatizing law through arbitration, but contends that we undervalue the costs of doing so. In particular, he expresses “grave doubts about the wisdom of balkanizing the adjudication of basic legal rights in private courts defined by a common membership in a particular cultural group.” Krotoszynski favors assimilation over separation, and worries that privatizing law through arbitration will impede assimilation. Relatedly, he worries that privatizing law through arbitration “would tend to exacerbate, rather than reduce, the legitimacy problems that the federal and state courts currently face.” As more of a group’s disputes go to arbitration, courts become less skilled at handling that group’s disputes and less sensitive to that group, which in turn further lowers the court system’s reputation with that group . I will reply to these concerns in this brief article. Before doing so, however, I note that Professor Krotoszynski’s discussion of arbitration is merely a small part of a broader project, an article entitled The New Legal Process: Games People Play and the Quest for Legitimate Judicial Decision Making. That article counsels legal scholars to quit debating what constitutes substantive justice and to start focusing on procedural justice. Because devotees of Critical Legal Studies and Law & Economics, for instance, will never agree on the conclusions judges should reach, Crits and economists should put aside those substantive differences and join together to pursue “a project dedicated to defining how judges should go about their task.” In other words, Krotoszynski’s article calls for nothing less than a reversal of the direction legal scholarship has taken for at least a generation. Krotoszynski’s article is ambitious. It is also erudite and witty. It deserves to be read in its entirety and deserves thoughtful consideration by those who can address its vast reach. At this time, however, I am prepared to address only its concerns about privatizing law through arbitration.
Keywords: Arbitration & award; Majoritarianism; Commercial arbitration; Dispute resolution (Law)